Inhibition of mmp13a during zebrafish fin regeneration disrupts fin growth, osteoblasts differentiation, and Laminin organization. Issue 2 (18th September 2019) - Li, Li; Zhang, Jing; Akimenko, Marie‐Andrée
Abstract: Background: Matrix metalloproteinases 13 (MMP13) is a potent endopeptidase that regulate cell growth, migration, and extracellular matrix remodeling. However, its role in fin regeneration remains unclear. Results: mmp13a expression is strongly upregulated during blastema formation and persists in the distal blastema. mmp13a knockdown via morpholino electroporation impairs regenerative outgrowth by decreasing cell proliferation, which correlates with a downregulation of fgf10a and sall4 expression in the blastema. Laminin distribution in the basement membrane is also affected in mmp13a MO‐injected rays. Another impact of mmp13a knockdown is observed in the skeletal elements of the fin rays. Expression of two main components of actinotrichia, Collagen II and Actinodin 1 is highly reduced in mmp13a MO‐injected rays leading to highly disorganized actinotrichia pattern. Inhibition of mmp13a strongly affects bone formation as shown by a reduction of Zns5 and sp7 expression and of bone matrix mineralization in rays. These defects are accompanied by a significant increase in apoptosis in mmp13a MO‐injected fin regenerates. Conclusion: Defects of expression of this multifunctional proteinase drastically affects osteoblast differentiation, bone and actinotrichia formation as well as Laminin distribution in the basement membrane of the fin regenerate, suggesting the important role of Mmp13 during the regenerative process. Key Findings: Our results suggest for the first time a role for Mmp13 in the regulation of the regeneration processes in zebrafish fin. mmp13a is sharply upregulated in the distal blastema of amputated fins. Inhibition of mmp13a reduces regenerative outgrowth of fins by decreasing blastema cell proliferation. Defects in mmp13a expression affect normal actinotrichia and bone formation. Mmp13a is involved in maintenance of basement membrane integrity during epidermis regeneration.